Studying geotectonics of continental and oceanic plates based on high-precision geodesic measurements from spacecraft - Udintsev, G. B.; Bagrov, A. V. (Ukrainian Antarctic Journal, 2012)
Space experiment to study the tectonics of oceanic lithospheric plates in their relations with the continental lithosphere-mantle massifs was proposed. It opens new interesting prospects for a detailed map creating of the solid Earth geokinematics in the oceans. The measurements of geodetic coordinates of points on the islands, rocks and reefs are required for the solution of the mentioned above problem. More important the repeatable data from the points on the islands which should reveal the kinematics of the ocean plates. The required accuracy can be achieved by special optical interferometer which proposed the Institute of Astronomy of RAS.